Ultrasonography, contrast-enhanced ultrasonography and contrast-enhanced computer tomography features of hepatic sarcomatoid carcinoma and hepatic sarcoma: a retrospective study of 23 cases - Xingyun Long; Haiyun Shen; Jie Wu; Han Liu; Danqing Huang; Wentao Kong (BMC Cancer)
Abstract Background Hepatic sarcomatoid carcinoma (HSC) and hepatic sarcoma (HS) are rare malignancies. Without pathology, the differential diagnosis between these two tumors is difficult due to their frequent overlaps in clinical presentations and imaging features. Currently, there are limited analyses about the ultrasound (US), contrast-enhanced ultrasound (CEUS) and contrast-enhanced computer tomography (CECT) characteristics of HSC and HS. Therefore, the purpose of our study is to evaluate the value of US, CEUS and CECT on the differential diagnosis between HSC and HS. Methods From 2015 to 2022, a total of 23 patients with HSC (n = 11) and HS (n = 12) are included in this retrospective study. We analyze the clinical, pathological, and imaging data of these patients. Analysis of differences is performed to determine the consistent and distinctive features. Results HSCs have a considerably higher prevalence of chronic hepatitis (p = 0.005) and cirrhosis (p = 0.027) than HSs, while metastases are more prevalent in HSs (p = 0.005). The lesion size of HSCs (8.1 ± 2.2 cm) is slightly larger than that of HSs (6.2 ± 3.4 cm). On conventional US, the characteristics of HS and HSC are similar. In CEUS, HSCs consistently showed heterogeneous enhancement patterns, while HSs, particularly hepatic angiosarcoma (HA), demonstrated a higher prevalence of hyperintensity (75%). On CECT, all masses in both groups exhibited low density. A statistically significant difference in margin clarity was observed between HSC and HS (p = 0.015). Conclusion HSC and HS generally present as masses with hypo-echoic and hypo-vascularity. HSC usually presents heterogeneous density. The degree of enhancement, the time of wash-out start, and the presence of necrotic areas may contribute to distinguish the different pathological types of HS.